Academic Whatsapp Group: Exploring Students’ Experiences in Writing Class - Fatimah Mulya Sari; Shely Nasya Putri (TEKNOSASTIK, 2019)
The use of social-networking application such as WhatsApp in learning writing enables students to foster individual learning experiences during the class and after the class. WhatsApp itself has a special feature to create the specific group in order to bound the members and intimate the interaction among lecturer and students relating to the course matters. This current study generally explores the students’ perceptions in experiencing WhatsApp Group Chat in learning writing. This qualitative research was conducted in one of universities in Lampung province, Indonesia. The subjects were 28 second year undergraduate students who enrolled writing course. The data used were questionnaire, interview, and observations. The findings present the multitude of views that most students significantly showed positive result to use WhatsApp Group in their writing class. By experiencing WhatsApp Group Chat in their learning writing, the students admitted that it is user-friendly and easy to use because it can intensify the interaction with the other group members during the class and after the class, be effective in submitting the writing assignment by uploading the file in the group, get the lecturer’s feedback directly after submitting the writing assignment, and freely ask and share the writing materials. However, some students also revealed that there were some technical problems found when they used the WhatsApp Group Chat such as abundant chats, poor signal, and junks notification. Nevertheless, learning writing through these cross-platform instant messaging might broaden the student’s self-learning experiences.Keywords: Students’ experience, WhatsApp Group, writing class